Retoryka i oralność: przypomnienia - Lichański, Jakub Zdzisław (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The aim of this paper is to remind the reader of the connections between the theories of rhetoric and orality. Using the example taken from the work of Edmund Rosalind, the author presents how orality influences the understanding of the text. In the conclusion the authorshows that an awareness of the importance of a vocal interpretation of the text has always accompanied the theory of rhetoric.
Keywords: rhetoric; orality; semantics; Milman Parry; WalterJ. Ong; Edmund Rostand